Spectrum Analysis of Inherited Metabolic Disorders for Expanded Newborn Screening in a Central Chinese Population - Li, Xia; He, Jun; He, Ling; Zeng, Yudong; Huang, Xuzhen; Luo, Yechao; Li, Yujiao (Frontiers in Genetics, 2022)
Neonatal inherited metabolic disorders (IMDs) are closely associated with early neonatal death and abnormal growth and development. Increasing attention has been paid to IMDs because of their high incidence and diversity. However, there are no reports about the prevalence of IMDs in Changsha, China. Therefore, we retrospectively analyzed the screening results of neonates to evaluate the characteristics of IMDs in the area. From January 2016 to December 2020, 300,849 neonates were enrolled for expanded newborn screening by tandem mass spectrometry in the Neonatal Disease Screening Center of the Changsha Hospital for Maternal & Child Health Care. Newborns with mild initial results were recalled for repeated tests; if the second test was still positive, the patient was referred for confirmatory tests. A total of 71 confirmed cases were identified in our study, with an incidence rate of 1:4,237. There were 28 cases of amino acid metabolic disorders, representing 39.44% of the IMDs diagnosed, with an incidence rate of 1:10,745. Twelve newborns were diagnosed with organic acid metabolic disorders, accounting for 16.66% of IMDs, with an incidence rate of 1:25,071. There were 31 cases of fatty acid oxidation disorders, representing 43.05% of IMDs, with an incidence rate of 1:9,705. Overall, 14 types of IMDs were found in Changsha. The most common disorders in the region were primary carnitine deficiency, hyperphenylalaninemia and short-chain acyl-CoA dehydrogenase deficiency. Their incidence rate is respectively 1:13,675, 1:16,714 and 1:42,978. The mutations in PAH, SLC22A5, and ACADS are the leading causes of IMDs in this area. This study demonstrates the importance of utilizing MS/MS in IMD screening for early diagnosis and treatment. This strategy may be used for prenatal genetic counseling to avoid irreversible growth and intellectual development disorders in children.